Bibliometric analysis of Central European journals in the Web of Science and JCR Social Science Edition - Bucher, SlavomÃr (Malaysian Journal of Library and Information Science, 2018)
This paper deals with the multi-perspective bibliometric analysis of Central European scientific journals indexed in the Web of Science database and covered in the Journal Citation Reports – Social Science Citation Index (SSCI). The analysis focuses on the evaluation of the (inter) national orientation of Central European Social Science journals indexed in the period 2012 – 2015. Data were obtained from the Web of Science database on October 20, 2016. The journals are divided in two groups in favour of the scientific discipline identifying the journal in the Web of Science. The first group consists of journals belonged to public health and psychology. The second group includes all social related scientific journals covered in both the SSCI and Science Citation Index Expanded (SCIE) databases. Journals were chosen by language versions of journals in the Web of Science, language versions of articles, authors’ most important institutional affiliations; and other statistically significant indicators provided by Clarivate Analytics. Assessment of the “openness of Central European journals” to foreign authors was analyzed on the basis of the “INO indicator” (Index of National Orientation). Statistical analyses were conducted on the articles which carry the relevant scientific information. Descriptive statistics was used for the data analysis, using frequencies, percentages and means. The results of this research showed a strong orientation towards Slovakian and Czech authors regardless of the two analyzed groups. Based on INO, most of the Central European journals quality and impact were comparatively low. A competitive environment has been created for journals in the social science disciplines, especially for those with competitors in neighboring countries in fields such as psychology, economics, geography and sociology.